Colaborative E-Business and software agents - Bernuy Alva, Augusto (2007)
The paper proposes the functions for two new agents in collaboration e-business, since we know that collaborative processes are growing up and we have a large way to work on researches about e-business. The start point is after we identify collaboration among people, processes and systems, we believe that each important process of the organization during its daily routine has two elements like context and content joined to the process. Then, we can understand those processes are important when you look at them as a result for another one and it can resolve a specific problem. We want to get the ability to collaborate and leverage the knowledge. We have been based the analysis on the intangibles assets joined with the technology in order to build a design to understand the collaborative e-business processes. We present the results of the process and collaboration that already exist between themselves each time when a task has been started, in order to obtain new knowledge. To do that, we are based in new DirCCI model for collaboration of intellectual capital, where the business needs and collaboration are defined and then we propose the concepts to design and understand the main elements of the new system. The result is a new way to understand collaboration based on software agents in order to gain significant and sustainable competitive advantage and knowledge management in the organizations and now we should think in how help people, processes and systems to think about virtual decisions through e-business.